Trans-boundary PM10: Quantifying impact and sources during winter 2016/17 in eastern Germany. (1st March 2019) - van Pinxteren, Dominik; Mothes, Falk; Spindler, Gerald; Fomba, Khanneh Wadinga; Herrmann, Hartmut
Abstract: Trans-boundary PM10 transport into eastern Germany was quantified by comparing mean PM10 concentrations during western and eastern air mass inflow under similar meteorological conditions and calculating an "increment East" as a proxy for the trans-boundary PM10 fraction. Data of 10 measurement stations located in Berlin, Brandenburg, Mecklenburg-Western Pomerania and Saxony were used for winter 2016/17 and revealed trans-boundary PM10 increments of 0–30 μg m −3 on average, depending on meteorological conditions. On average over all days with positive increments, trans-boundary transport contributed 13 μg m −3 or 44% to the total PM10 concentration in the regional background. During pollution periods with elevated PM10 concentrations of >30 μg m −3 at rural background sites, this contribution lied between 44 and 62%, while it decreased to about 20% for moderate PM10 concentrations between 20 and 30 μg m −3 and was negligible for PM10 concentrations <20 μg m −3 . Based on its chemical composition, PM10 was apportioned to 6–7 different sources by positive matrix factorisation (PMF) receptor modelling. It was found that typically >80% of the trans-boundary PM10 fraction imported from eastern neighbouring countries can be explained by combustion emissions and formation of secondary particle mass, i.e. ammonium sulfate and organic matter, with the latter typically exceeding the contributions from combustion. Source contributions of these two PMF factors within the increment East were correlated, indicating combustion-related emissions of SO2 and volatile organic compounds leading to the observed secondary trans-boundary PM10 mass. Higher increment East values for cold than for warm days imply emissions from domestic heating in eastern European countries, presumably from the combustion of solid fuels such as wood and coal, as the dominant source for trans-boundary PM10 in eastern Germany. A case study for a traffic-impacted pollution hotspot in the city of Berlin showed an average contribution of about 30% from trans-boundary transport, while regional background, urban background and local traffic emissions explained about 40, 10, and 20% of PM10 mass concentrations during days with eastern air mass inflow where the increment East approach could be applied together with the incremental Lenschow approach. The results of this study reinforce the need of PM10 mitigation measures at different spatial scales, ranging from municipal to international levels. Graphical abstract: Highlights: Observations and receptor modelling were used to study trans-boundary PM10. Trans-boundary PM10 from eastern Europe was quantified to range from 0 to 30 μg m −3 Its contribution was 44–62% of total PM10 during pollution periods at rural sites. Main source was combustion emissions, likely from solid fuels for domestic heating.